Decision Process Evolution in Customer Channel Choice - Valentini, Sara; Montaguti, Elisa; Neslin, Scott A. (Journal of Marketing, 2011)
The growing number of sales channels through which customers can make purchases has made it imperative for managers to understand how customers decide which channels to use. However, this presents a significant challenge because there is reason to believe the channel decision process evolves over the lifetime of the customer. The authors document the existence and nature of this phenomenon by analyzing the evolution of a customer's channel choice decision process from a trial stage to a posttrial stage. First, they analyze data for a book retailer and replicate their analysis using data from a durables and apparel retailer. Their results suggest that (1) customers’ decision processes do evolve, (2) a minority but sizeable segment changes decision processes within the observation period, and (3) customers who change do so from a decision process in which they are highly responsive to marketing to one in which they are less responsive. The authors illustrate and discuss the implications for both managers and researchers.